«Català» i «valencià» al primer cinccents. A propòsit de dues edicions de l’«Spill de la vida religiosa» - Rafanell, August; Valsalobre, Pep (Caplletra. Revista Internacional de Filologia, 2017)
A comparative analysis of variants introduced in the Valencia edition of «Spill de la vida religiosa» (1529) in contrast to the Barcelona edition (1515), with recourse to analogous data from reprints of Hull or Eiximenis and from the «Regles» attributed to Fenollar-Pau. The authors conclude that the differences are superficial and reveal an eagerness to Valencianize, or rather modernize, which cannot be regarded, in any case, as symptom of language breaking up.